Evolution of epilepsy prevalence and incidence in a Tanzanian area endemic for onchocerciasis and the potential impact of community-directed treatment with ivermectin: a cross-sectional study and comparison over 28 years - Greter, Helena (BMJ Open, 2018)
INTRODUCTION: Worldwide, there are an estimated 50 million people affected by epilepsy. Its aetiology is manifold, and parasitic infections play an important role, specifically onchocerciasis. In onchocerciasis endemic areas, a distinctive form of epilepsy has been described as nodding syndrome, affecting children and causing nodding seizures, mental retardation and debilitating physical development. Onchocerciasis control programmes using community-directed treatment with ivermectin (CDTI) are implemented in endemic countries. This study is designed to contribute to a better understanding of the linkage between the onset of epilepsy, onchocerciasis and CDTI. Comparing the epidemiological data on epilepsy and onchocerciasis from pre-CDTI and 20 years after its introduction will allow identifying a potential impact of ivermectin on the onset of epilepsy. METHODS AND ANALYSIS: The study will be conducted in the Mahenge highlands in Tanzania. Study site selection is based on an in-depth study on epilepsy in that area dating from 1989. CDTI was introduced in 1997. By a door-to-door approach, the population will be screened for epilepsy using a validated questionnaire. Suspected cases will be invited for a neurological examination for case verification. Onchocerciasis prevalence will be assessed by a rapid epidemiological assessment. As an indicator for ongoing transmission, children younger than 10 years of age will be tested for Ov16 antibodies. Ivermectin use will be assessed at household level. Epilepsy data will be analysed in comparison with the 1989 data to reveal pre-CDTI and post-CDTI prevalence and incidence. ETHICS AND DISSEMINATION: The protocol has received ethical approval from the ethics committees of the University of Antwerp, Belgium, and of the National Institut of Medical Research, Dar es Salaam, Tanzania. The findings will be published in peer-reviewed journals, and presented to the health authorities in Tanzania, at national, regional and village level.